Immunogenomic Profiling Demonstrate AC003092.1 as an Immune-Related eRNA in Glioblastoma Multiforme - Guo, Xiao-Yu; Zhong, Sheng; Wang, Zhen-Ning; Xie, Tian; Duan, Hao; Zhang, Jia-Yu; Zhang, Guan-Hua; Liang, Lun; Cui, Run; Hu, Hong-Rong; Lu, Jie; Wu, Yi; et al. (Frontiers in Genetics, 2021)
Enhancer RNAs, a type of long non-coding RNAs (LncRNAs), play a critical role in the occurrence and development of glioma. RNA-seq data from 161 glioblastoma multiforme (GBM) samples were acquired from The Cancer Genome Atlas database (TCGA). Thereafter, 70 eRNAs were identified as prognosis-related genes which had significant association with overall survival (Log-Rank test, p < 0.05). AC003092.1 was then identified as an immune-related eRNA using functional enrichment analysis. We divided samples into two groups based on AC003092.1 expression: AC003092.1 High (AC003092.1_H), and AC003092.1 Low (AC003092.1_L) and systematically analyzed the influence of AC003092.1 on the immune microenvironment using ssGSEA and CIBERSORTx. Finally, we quantified AC003092.1 and TFPI2 levels in 11 high-grade gliomas, 5 low-grade gliomas, and 7 GBM cell lines. Our study indicates that AC003092.1 is associated with glioma immunosuppressive microenvironment and these results offer innovative insights into GBM immune therapy